Acceleration of rural households' conversion to cleaner cooking fuels: The importance and mechanisms of peer effects. (July 2021) - Wen, Hong-xing; Wang, Chan; Nie, Pu-yan
Abstract: This study investigated the existence of peer effects in the diffusion of clean cooking fuels among rural households in China and identified the mechanisms by which these peer effects were enacted from the perspective of social networks. We observed greater adoption of clean cooking fuels in areas in which adoption was already relatively high, however, this peer spill-over decreased over time and was regulated by the accessibility and strength of social networks. Specifically, if a household's social circle was more extensive or its communication with neighbours, relatives, and friends was closer, its choice of a clean cooking fuel was more likely to be affected by its peer groups. To stimulate stronger peer spill-over, we suggest that interventions such as strengthening social interactions across rural households should be included in the government's strategy to help more households convert to cleaner cooking fuels. Highlights: It is the first to prove peer effects exist in the diffusion of clean cooking fuels. Peer effects decrease over time during 2010–2018. Peer effects are regulated by the accessibility and strength of social networks. Strengthening social interactions helps to stimulate stronger peer spill-over. Clean cooking policies should consider peer spill-over and social interactions.